Inflation and wage indexation in Italy - FAZIO, A. (PSL Quarterly Review, 2013)
The present paper traces the development in inflation in Italy throughout the period following WWII, with particular emphasis on its relation to labour costs, productivity and import prices. Since the sliding scale mechanism has been operating at full power during the whole of the seventies, and especially in the second half of the decade, owning to the increased frequency of both domestic and imported destabilising pressures, this period is analysed in greater detail. The conclusions indicate that the sliding scale has played an important role in aggravating inflationary pressures during that period. JEL: E31, N14